Perioperative and persistent opioid use after surgery: a scoping review - Bader Almodibeg; Jungwoo Kang; Patrice Forget (BJA Open)
Persistent opioid use after surgery is a growing concern, with existing reviews lacking strong predictors beyond prior opioid use. This scoping review aimed to identify knowledge gaps for future research, particularly regarding the impact of the perioperative period (including preoperative, intraoperative, and postoperative) opioid use on persistent opioid use after surgery. A comprehensive database search of prospective studies explored the association between perioperative opioid use and persistent use in adults after surgery. From the 21 identified studies, we found a complex relationship between perioperative opioid use and persistent use. Preoperative opioid use correlated with persistent use, but the impact of intraoperative and short-term postoperative use remained unclear. Interestingly, postoperative prescriptions at 3 months predicted a higher risk of persistent use at 6 and 12 months. These findings highlight the need for further research to explore the mediating factors that increase the risk of persistent use among preoperative opioid users, along with the specific roles of intraoperative and postsurgical inpatient opioid consumption, and short-term postoperative opioid prescriptions (≤30 days).